A Bubble‐Assisted Approach for Patterning Nanoscale Molecular Aggregates. (15th June 2021) - Min, Fanyi; Zhou, Peng; Huang, Zhandong; Qiao, Yali; Yu, Changhui; Qu, Zhiyuan; Shi, Xiaosong; Li, Zheng; Jiang, Lang; Zhang, Zhen; Yan, Xuehai; Song, Yanlin
Abstract: We demonstrate a new approach to pattern functional organic molecules with a template of foams, and achieve a resolution of sub 100 nm. The bubble‐assisted assembly (BAA) process is consisted of two periods, including bubble evolution and molecular assembly, which are dominated by the Laplace pressure and molecular interactions, respectively. Using TPPS (meso‐tetra(4‐sulfonatophenyl) porphyrin), we systematically investigate the patterns and assembly behaviour in the bubble system with a series of characterizations, which show good uniformity in nanoscale resolution. Theoretical simulations reveal that TPPS's J‐aggregates contribute to the ordered construction of molecular patterns. Finally, we propose an empirical rule for molecular patterning approach, that the surfactant and functional molecules should have the same type of charge in a two‐component system. This approach exhibits promising feasibility to assemble molecular patterns at nanoscale resolution for micro/nano functional devices. Abstract : A new approach to pattern functional organic molecules with a template of foams has been developed, and this approach can achieve a resolution of sub 100 nm currently. Using a kind of water‐soluble porphyrin, we elucidate the hierarchal assembly structure and molecular interactions in bubble system.